1998
DOI: 10.1046/j.1365-2605.1998.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlormadinone acetate pellet implantation plus short‐term oral administration in dogs with benign prostatic hypertrophy

Abstract: Eight beagles with benign prostatic hypertrophy (BPH) were treated by subcutaneous implantation of pellets containing 10 mg/kg chlormadinone acetate (CMA), a synthetic anti-androgen, plus daily oral administration of CMA at 2 mg/kg per day for 7 days as a therapy for BPH. Prostatic and testicular size were measured and prostatic and testicular biopsies were performed by laparotomy before and after CMA treatment. Plasma levels of luteininzing hormone (LH), testosterone and oestradiol were also measured. The cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In treatment of BPH, because the prostate is an androgen (A)-dependent organ, orchidectomy [11] or treatment with anti-A agents [1,3] is performed. We previously showed that oral administration of chlormadinone acetate (CMA), which is a commercially available anti-A agent for human use, improved clincial symptoms during the early phase of BPH [4,10]. However, we also reported that the size of the prostate returned to the same size as that prior to administration 12 weeks later [10].…”
mentioning
confidence: 97%
“…In treatment of BPH, because the prostate is an androgen (A)-dependent organ, orchidectomy [11] or treatment with anti-A agents [1,3] is performed. We previously showed that oral administration of chlormadinone acetate (CMA), which is a commercially available anti-A agent for human use, improved clincial symptoms during the early phase of BPH [4,10]. However, we also reported that the size of the prostate returned to the same size as that prior to administration 12 weeks later [10].…”
mentioning
confidence: 97%
“…Daily oral administration of CMA for several weeks caused atrophy of the glandular alveoli in dogs with BPH [22]. The combination of a tablet for internal use and a pellet for s.c. use successfully achieved an early resolution in dogs with BPH [23]. In a rat model, there was a reduction of the capillary luminal area of the prostate, as assessed by transmission electron microscopy, after 5 days of CMA treatment, suggesting that the action of androgens is directly inhibited by CMA at the cellular level, and decreases blood supply to the prostate as a result [24].…”
Section: Discussionmentioning
confidence: 99%
“…There are limitations to the present study; the size and condition of the prostate are evidently different between normal rats and patients with BPH or prostatic cancer in the clinical setting. Animal experiments on prostate treatment were reported for dogs with spontaneous BPH [21–23], normal rats [24,27], and nude mice [28], using the i.v. [28] and s.c. routes [27,29].…”
Section: Discussionmentioning
confidence: 99%